Ab initio thermodynamics reveals the nanocomposite structure of ferrihydrite - Michel Sassi (Nature Portfolio, 2021)
Ferrihydrite is the most bioavailable source of ferric iron, but its variable structure and composition are poorly understood because of its small size and lack of ordering. Here ab initio thermodynamics reveals that ferrihydrite can be described as a nanocomposite of at least two previously-proposed single-phase models.